Engaging a state: Facebook comments on a large population biobank - Platt, Tevah (J Community Genet, 2017)
Scholarship on newborn screening, dried bloodspot retention, and large population biobanking call consistently for improved public engagement. Communication with participants likely occurs only in the context of collection, consent, or notification, if at all. We ran an 11-week advertising campaign to inform Michigan Facebook users unlikely to know that their or their children’s dried bloodspots (DBSs) were stored in a state biobank. We investigated the pattern and content of comments posted during the campaign, focusing on users’ questions, attitudes and concerns, and the role the moderator played in addressing them. We used Facebook data to quantitatively assess engagement and employed conventional content analysis to investigate themes, attitudes, and social dynamics among user and moderator comments. Five ad sets elicited comments during campaign weeks 4–8, reaching ∼800,000 Facebook users ($6000). Gravitating around broad, underlying ethical, legal, and social issues, 180 posts from 129 unique users related to newborn screening or biobanking. Thirty six conveyed negative attitudes and 33 conveyed positive attitudes; 53 posed questions. The most prevalent themes identified were consent, privacy, bloodspot use, identifiability, inclusion criteria, research benefits, (mis)trust, genetics, DBS destruction, awareness, and the role of government. The moderator’s 81 posts were responsive—answering questions, correcting or clarifying information, or providing information about opting out. Facebook ad campaigns can improve engagement by pushing out relevant content and creating dynamic, responsive, visible forums for discussion. Reduced control over messaging may be worth the trade-off for creating accessible, transparent, people-centered engagement on public health issues that are sensitive and complex. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12687-017-0302-z) contains supplementary material, which is available to authorized users.